2019
DOI: 10.1038/s41598-019-48262-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of nobiletin on isolated human islets survival and function against hypoxia and oxidative stress-induced apoptosis

Abstract: Islets transplantation, as a treatment of type 1 diabetes, faces challenges, including the loss of islets in the process of isolation and pre-transplantation due to cellular stresses-induced apoptosis. Accordingly, the optimization of culture plays a decisive role in the transplantation success. In this study, we evaluated the effect of nobiletin on the cultured human islets. Isolated human islets were treated by different concentrations of nobiletin and cultured for 24 and 72 hours. Then, the islets viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Imaging was performed using a fluorescence microscope (CKX53, Olympus, Japan). The viability rate was expressed by the percentage of green area to the total area within intact islet (Keshtkar et al, 2019[ 19 ]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging was performed using a fluorescence microscope (CKX53, Olympus, Japan). The viability rate was expressed by the percentage of green area to the total area within intact islet (Keshtkar et al, 2019[ 19 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Type 1 diabetes comprises 5-10 % of all diabetic cases and is the consequence of the autoimmune destruction of pancreatic beta cells, giving rise to absolute insulin deficiency (Keshtkar et al, 2019[ 19 ]; You and Henneberg, 2016[ 43 ]). Islet transplantation is considered a promising treatment for type 1 diabetes patients who face severe periods of hypoglycemia (Saravanan et al, 2017[ 33 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that NOB inhibited apoptosis induced by thapsigargin in INS-1D β-cells [15] and hypoxia/reoxygenation in H9c2 cardiomyocytes [16]. After islets transplantation in humans, apoptosis of isolated islets cells could also be ameliorated by NOB [17]. rational to hypothesize that NOB might induce apoptosis in BeWo cells.…”
Section: Introductionmentioning
confidence: 98%
“…The isolation process of the human pancreatic islets from their niche leads to loss of biological and mechanical support of the cells. In this stressful situation, the apoptosis is activated in the islets; hence, eliminating this process becomes critical in order to reduce the number of tissues needed for pancreatic islet transplantation (1)(2)(3)(4). Tissue engineering is an attractive strategy for remodeling extracellular matrix (ECM) and improving the culture and transplantation methods.…”
Section: Introductionmentioning
confidence: 99%